2021
DOI: 10.1186/s12903-021-01428-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19-imposed lockdown and online searches for toothache in Iran

Abstract: Background Novel coronavirus disease-2019 (COVID-19) has impacted populations in many ways worldwide, including access to oral health services. This study aims to assess the association between lockdown due to COVID-19 and online searches for toothache in Iran using Google Trends (GT). Methods We investigated GT online searches for toothache within the past five years. The time frame for data gathering was considered as the initiation and end dates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…Hence finally, one paper had shared data (0.2%). This article was published in BMC Oral Health in 2021 [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence finally, one paper had shared data (0.2%). This article was published in BMC Oral Health in 2021 [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The aim of the study was to investigate the impact of the COVID-19 pandemic on oral health and teledentistry subjects. To the best of our knowledge, this is one of the few studies [19,20] tracing the GT expressions connected with oral health during the COVID-19 pandemic. The first noticeable outcome of the research was a large increase in emergency dental care questions asked during the spring lockdown in 2020 with a simultaneous decrease in regular dental care queries.…”
Section: Discussionmentioning
confidence: 99%
“…Using the trends of Google search engine (Google Inc.; Mountain View, California USA), with around four billion users world-wide, two recent studies found a steep upward trend in online searches for dental problems and tele-dentistry. 13,14 Additionally, a fivefold increase in the number of searches for "tele-dentistry" and a 30-fold increase for "PPE https://doi.org/10.1017/S1049023X22001339 Published online by Cambridge University Press dentist" were recorded. Moreover, a 40-fold increase in the question "is it safe to go to the dentist" showed a high level of fear of going to the dentist.…”
Section: Dear Editormentioning
confidence: 99%